The age of the ferropicritic volcanics and comagmatic Ni-bearing intrusions at Pechenga, Kola Peninsula, U.S.S.R. - E. Hanski; H. Huhma; V.F. Smolkin; M. Vaasjoki (Bulletin of the Geological Society of Finland, 1990)
Sm-Nd, Pb-Pb and U-Pb isotopic results are presented for samples from the Pilgujärvi Suite of the Pechenga Series. Whole rock samples and clinopyroxenes of ferropicritic volcanics yield a Sm-Nd isochron age of 1990 ± 66 Ma with εNd + 1.6 ± 0.4. This age is also supported by the Pb-Pb data on ferropicrites, although the Pb isotopic system was partly disturbed by secondary processes. One 90% concordant U-Pb zircon analysis from a felsic metasediment indicates a minimum age of 1970 Ma for the deposition. Our isotopic results along with previous geochemical data support the view that the ferropicritic volcanics and the Ni-bearing gabbro- wehrlite intrusions are coeval and have similar source characteristics. The calculated εNd (1990 Ma) value of + 1.6 suggests that the Pechenga ferropicrites previously had had a long-term depleted mantle source that experiended an enrichment event about 200 Ma before the melt extraction occurred. Comparison with the previously presented Sm-Nd data from northern Finland, Sweden and Norway reveals differences in initial Nd isotopic ratios, which suggests a prolonged geochemical heterogeneity in the early Proterozoic subcontinental mantle below the Baltic Shield.